The Protective Effect of Indole-3-Acetic Acid (IAA) on H(2)O(2)-Damaged Human Dental Pulp Stem Cells Is Mediated by the AKT Pathway and Involves Increased Expression of the Transcription Factor Nuclear Factor-Erythroid 2-Related Factor 2 (Nrf2) and Its Downstream Target Heme Oxygenase 1 (HO-1) - Kim, Daehwan (Oxid Med Cell Longev, 2017)
Indole-3-acetic acid (IAA) is the most common plant hormone of the auxin class and is known to have many effects including cell proliferation enhancement and antioxidant property. However, no study has revealed its defensive effects against oxidative toxicity in human dental pulp stem cells (hDPSCs). In this study, we investigated the effects of IAA on hydrogen peroxide- (H(2)O(2)-) induced oxidative toxicity in hDPSCs. H(2)O(2)-induced cytotoxicity was attenuated after IAA treatment. Cell cycle analysis using FACS showed that the damaged cell cycle and increased number of apoptotic cells by H(2)O(2) treatment were recovered after the treatment of IAA. The H(2)O(2)-mediated increased expression of the proapoptotic genes, BAX and p53, was attenuated by IAA treatment, while IAA treatment increased antiapoptotic genes, BCL-2 and ATF5 expression. The increases of cleaved caspase-3 and ROS by H(2)O(2) were also decreased after treatment of IAA. To further investigate the mechanism of IAA, Nrf2-related antioxidant pathway was examined and the results showed that the level of Nrf2 and HO-1 expressions, stimulated by H(2)O(2,) decreased after treatment of IAA. Moreover, IAA treatment protected hDPSCs against H(2)O(2)-induced oxidative stress via increased expression of Nrf2 and HO-1, mediated by the AKT pathway.